Akulturasi arsitektur lokal dan nonlokal pada elemen pelingkup Masjid Merah Panjunan di Cirebon - Arita; Hartanto Budiyuwono; Yuswadi Saliya (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Architectural acculturation has a significant and uniform impact on modern architecture. However, the misunderstanding of this phenomenon tends to occur due to its inability to match its context's function and meaning. Therefore, this study aims to examine the acculturation of local and non-local architecture in mosque buildings. Previous research only focuses on mosque buildings as a syncretic factor, with none on the attributed topic. The research object is the Merah Panjunan Mosque in Cirebon City. This object was chosen based on the building age, the acculturation phenomenon that occurs, and because it is one of the cultural heritage in Cirebon City. The research method includes redrawing the Merah Panjunan Mosque's entire mass in three and two dimensions, making it easy to parse based on architectural anatomy. The study object's decomposition is intended to facilitate analysis in each unit of architectural elements, which is read based on the elaboration of the balance and orientation principles. The analysis results are interpreted in the conclusion section with the Merah Panjunan Mosque capable of displaying local and non-local architecture characterized by Javanese and Chinese architectures as well as a Hindu temple. The dominant composition of the Merah Panjunan Mosque acculturation is shown in the roof elements. Therefore, this research implies that Merah Panjunan acts as a reference for architectural design with the acculturation concept.